Cover Picture: Orthorhombic HP‐REOF (RE = Pr, Nd, Sm – Gd) – High‐Pressure Syntheses and Single‐Crystal Structures (Z. Anorg. Allg. Chem. 20/2016). Issue 20 (14th October 2016) - Glätzle, Matthias; Schauperl, Michael; Hejny, Clivia; Tribus, Martina; Liedl, Klaus R.; Huppertz, Hubert
Abstract : The cover picture shows the crystal structure of the rare earth oxide fluorides HP‐ RE OF ( RE = Pr, Nd, Sm – Gd) and their formation out of the rare earth oxides and fluorides. By the application of a sophisticated high‐pressure/high‐temperature synthesis technique, the growth of single crystals of HP‐ RE OF ( RE = Nd, Sm, Eu) suitable for analyses via single crystal X‐ray diffraction was achieved, enabling a clear structural investigation of the one and only known high‐pressure rare earth oxide fluorides with ideal 1:1:1 stoichiometry for the first time. The compounds crystallize in the orthorhombic α‐PbCl2 ‐type structure (space group Pnma, No. 62, Z = 4) and are isostructural to the orthorhombic high‐pressure modifications of CaF2, CeO2, and PrO2 . The accurate single crystal X‐ray diffraction data combined with calculations of the bond‐valence sums allowed for a clear distinction of the fluorine and oxygen atom sites within the crystal structures. Details on the syntheses, structural investigations, elemental and vibrational analyses, as well as quantum mechanical calculations are given in the article by Matthias Glätzle et al. onp. 1134 ff .